The effect of climate on infection with hepatitis B virus in Maysan governorate for the period (2001-2020))) (Journal of the College of Basic Education, 2023)
Climate, with its basic elements (solar radiation, temperature, wind, air humidity and rain), is the most important component of the natural environment in which man lives, because of its effective impact on human health and various activities and infection with endemic diseases through its direct impact on pathogens and their vectors of insects and the reproduction of parasites and germs And viruses and in the multiplication of organisms that transmit diseases or store their microbes, as these appropriate climatic elements provide ideal conditions for pathogens, especially viral hepatitis B disease. Through the study, it appeared that climatic elements do not directly affect hepatitis B disease.